Association Between Anatomical Location and Hematoma Expansion in Deep Intracerebral Hemorrhage - Song, Lei; Qiu, Xiao-Ming; Guo, Ting-Ting; Zhou, Hang; Tang, Dong-Fang; Wang, Long-Sheng; Fu, Yu-Fei; Chen, Hui; Mao, Hua-Qing; Wang, Hai-Bao; Yu, Yong-Qiang (Frontiers in Neurology, 2022)
Objective: To establish the relationship between hematoma sites of involvement and hematoma expansion (HE) in patients with deep intracerebral hemorrhage (ICH). Methods: Eligible patients with deep ICH admitted to hospital within 6 hours of onset between 2018 and 2020 were included in this retrospective multi-center study. Individuals with secondary ICH were excluded. The volume of HE was evaluated based on admission and follow-up computed tomography scans. Associations between deep ICH sites of involvement and HE were examined using multivariable logistic regression analysis while adjusting for confounding covariates of HE. Results: We enrolled 583 individuals from three stroke centers. Data from a final total of 460 patients were used in the analysis; of these patients, 159 (34.6%) had HE. The analysis was fully adjusted for sex, age, intraventricular hemorrhage, Glasgow Coma Scale admission score, baseline ICH volume, and time from onset to initial computed tomography. The results revealed that the posterior limb of the internal capsule is a robust predictor of HE in patients with deep ICH (adjusted odds ratio = 2.73; 95% confidence interval = 1.75–4.26; p < 0.001). Conclusion: Involvement of the posterior limb of the internal capsule in deep hemorrhage could be a promising predictor of HE.